Zur Ingangsetzung von Attritionsprozessen in der Aussprache polnischer Lerner des Deutschen: Ergebnisse einer Pilotstudie zum Einfluss des Sprachleistungsniveaus - Długosz, Kamil (Instytut Germanistyki Uniwersytetu Warszawskiego, 2018)
Abstract Language attrition is a bilingual phenomenon, which covers regression in language representation and processing when language is not used for a certain period of time. Yet, little is known about foreign language attrition and attrition in pronunciation. This pilot study explores the first signs of language attrition processes in the pronunciation of six Polish adult learners of German who have not used German for two months. Two groups on levels B1 and C2 are examined on the basis of a reading task. The case proves the occurrence of attrition and reveals its symptoms. The findings also suggest a positive correlation between high level of language proficiency and possible prevention of attrition. The results are briefly discussed in light of the Activation Threshold Model (Paradis 2004, 2007) and the Regression Hypothesis. Finally, some implications for glottodidactics are offered in the article.
Keywords: Sprachattiriton; Psycholinguistik; Language attrition; Psycholinguistics; Aussprache; Pronunciacion; Activation Threshold Model; Regression Hypothesis; Mehrsprachigkeit; Bilingualism; Deutsch als Fremdsprache; Deutsch as foreign language